2002
DOI: 10.1590/s1517-83822002000300007
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenase activity of Beijerinckia derxii is preserved under adverse conditions for its growth

Abstract: In order to evaluate the response of Beijerinckia derxii ICB-10 to different environmental factors, growth curves and specific nitrogenase activity were studied. Tested conditions were as follows: a) media with different pH values (2.5, 2.8, 4.2 and 5.7); b) medium supplemented with 230 µM aluminium sulphate; c) media with two different potassium phosphate concentrations (50 mM and 100 mM); d) shaken or still cultures; e) medium supplemented with 40 mM sodium thiosulphate. Growth curves and specific nitrogenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In shaker conditions, the cells utilize growth nutrients faster and move early to the stationary phase, which results in the transition of older cells to stress conditions, leading to melanin production (Fig. 5) [10,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In shaker conditions, the cells utilize growth nutrients faster and move early to the stationary phase, which results in the transition of older cells to stress conditions, leading to melanin production (Fig. 5) [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…Barbosa et al [10] observed an increase in slime production and cell density in B. derxii over the time when glucose was the sole carbon source. Barbosa et al 2002, have also shown that co-factors like metal salts and aerobic conditions are essential for the cell growth and specific nitrogenase activity of B. derxii strain ICB-10 [11]. Becking, observed that Beijerinckia species grow in the pH range of 3.0 to 9.0 at an optimal temperature of 25 ° C to 30 ° C [12,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Acid tolerant strains Beijerinckia derxii racts differently to aluminium. Barbosa et al, (2002) observed that a decline in the number of CFU was observed immediately after the end of the exponential phase.…”
Section: Effects Of Aluminium On Azotobactermentioning
confidence: 97%
“…Within the catalytic MoFe protein, the M-cluster is ligated by an organic homocitrate and two residues: C275 and H442. Structural homologs to the M-cluster consist of the native V-cluster [VFe7S9C] (substitution of molybdenum with vanadium) and symmetric L-cluster [Fe8S9C] (Georgiadis et al, 1992;Barbosa et al, 2002;Huang et al, 2021). In all nitrogenase systems, Fe proteins couple the transfer of an electron achieved from either a ferredoxin or a flavodoxin to their cognate dinitrogenase (MFe protein, with M = Mo, V or Fe) to the hydrolysis of two molecules of ATP per electron; three dimensional structure of the complex of the two constituents of Mo-nitrogenase, Fe protein NifH, and the MoFe protein NifDK, and the complex is shaped transiently for each single electron transfer and the overall reaction demands at least 8 electrons per N2 (Trncik et al, 2022).…”
Section: Structure Of Nitrogenase Structure Of Nitrogenase Structure ...mentioning
confidence: 99%
“…The nitrogenase enzyme complex (the nitrogen, fixing enzyme) is sensitive to O2, that irreversible inactivates the enzyme, and diazotrophs must engage in mechanisms which on the other hand allow the supply of O2 required for energy regeneration and protect Nase from the deleterious impacts of O2, and they have developed diverse ways for limiting O2 access to Nase: 1) It could avoid O2 and live in environments which are constantly anaerobic, 2) Alternatively, it could generate a physical barrier around its Nase and in this way block O2 from diffusing to the enzyme, 3) The microorganism could, but its metabolism, decrease the concentration of O2 within the vicinity of Nasa, 4) They could adjust its Nasa in such manner as to render it resistant to inactivation by O2 (conformational protection), 5) Finally, the microorganism could merely balance Nasa inactivation with the synthesis of new enzyme (Miller and Orme-Johnson, 1992;Soto-Urzua and Baca, 2001;Byer et al, 2015). Nitrogenase activity was always maintained even when population growth was influenced, and the stimulus may be very high during the stationary or death steps, conditions in which bacteria are frequently found in the environment (Richards, 1996;Barbosa et al, 2002). Nitrogenases are composed of two protein that can be purified individually: dinitrogenase and dinitrogenase reductase (Bulen and LeComte, 1966;Hageman and Burris, 1978;Barriere et al, 2001).…”
Section: Action Mechanism Of Nitrogenase Action Mechanism Of Nitrogen...mentioning
confidence: 99%